CHEK2*1100delC heterozygosity in women with breast cancer associated with early death, breast cancer-specific death, and increased risk of a second breast cancer - Weischer, Maren; Burwinkel, Barbara; Marmé, Frederik; Sohn, Christof (Journal of clinical oncology, 2012)
Purpose We tested the hypotheses that CHEK2*1100delC heterozygosity is associated with increased risk of early death, breast cancer-specific death, and risk of a second breast cancer in women with a first breast cancer. Patients and Methods From 22 studies participating in the Breast Cancer Association Consortium, 25,571 white women with invasive breast cancer were genotyped for CHEK2*1100delC and observed for up to 20 years (median, 6.6 years). We examined risk of early death and breast cancer-specific death by estrogen receptor status and risk of a second breast cancer after a first breast cancer in prospective studies. Results CHEK2*1100delC heterozygosity was found in 459 patients (1.8%). In women with estrogen receptor-positive breast cancer, multifactorially adjusted hazard ratios for heterozygotes versus noncarriers were 1.43 (95% CI, 1.12 to 1.82; log-rank P = .004) for early death and 1.63 (95% CI, 1.24 to 2.15; log-rank P < .001) for breast cancer-specific death. In all women, hazard ratio for a second breast cancer was 2.77 (95% CI, 2.00 to 3.83; log-rank P < .001) increasing to 3.52 (95% CI, 2.35 to 5.27; log-rank P < .001) in women with estrogen receptor-positive first breast cancer only. Conclusion Among women with estrogen receptor-positive breast cancer, CHEK2*1100delC heterozygosity was associated with a 1.4-fold risk of early death, a 1.6-fold risk of breast cancer-specific death, and a 3.5-fold risk of a second breast cancer. This is one of the few examples of a genetic factor that influences long-term prognosis being documented in an extensive series of women with breast cancer.
Gesehen am 13.05.2019